2020
DOI: 10.1097/aln.0000000000003283
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Morphine versus Intrathecal Hydromorphone for Analgesia after Cesarean Delivery

Abstract: Background Intrathecal opioids are routinely administered during spinal anesthesia for postcesarean analgesia. The effectiveness of intrathecal morphine for postcesarean analgesia is well established, and the use of intrathecal hydromorphone is growing. No prospective studies have compared the effectiveness of equipotent doses of intrathecal morphine versus intrathecal hydromorphone as part of a multimodal analgesic regimen for postcesarean analgesia. The authors hypothesized that intrathecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 21 publications
(30 reference statements)
1
30
1
3
Order By: Relevance
“…In the study of 80 patients undergoing laparoscopic gynecological surgery, Zhang [17] also found that intravenous injection of hydromorphine hydrochloride into 15 min before the end of the operation, did not prolong the extubation time and did not increase the incidence of postoperative respiratory depression, which supported the results of this study.…”
Section: Resultssupporting
confidence: 82%
“…In the study of 80 patients undergoing laparoscopic gynecological surgery, Zhang [17] also found that intravenous injection of hydromorphine hydrochloride into 15 min before the end of the operation, did not prolong the extubation time and did not increase the incidence of postoperative respiratory depression, which supported the results of this study.…”
Section: Resultssupporting
confidence: 82%
“…11 Intrathecal hydromorphone has previously been described in adults with similar efficacy and safety. 12 We reported pain score trends looking specifically at single-shot Of note, although the majority of our patient population had STSG from below the waist where the spinal local anesthetic could provide analgesic coverage, approximately one third had donor skin taken above the umbilicus, which would not be covered. Thus, it appears that the addition of an intrathecal opioid to the single-shot spinal provides effective analgesia for donor sites not covered by the local anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed no difference in the analgesia produced by hydromorphone and that of morphine. Although hydromorphone also carries significant addiction potential, the result confounded researchers' expectation that morphine would produce better anesthesia (66). Although it does not directly compare morphine to a non-opioid drug, this study is likely to invite further inquiries testing long-held assumptions about the applications of opioids to surgical pain.…”
Section: Conventional Assumptions About Relative Efficacymentioning
confidence: 99%